Spatial analysis of soil parameters in Domagor-Pahuj watershed using Geostatistical methods of GIS - RIZVI, R H; YADAV, R S; SINGH, RAMESH; PANDEY, S B; WANI, S P; DHYANI, S K (The Indian Journal of Agricultural Sciences, 2015)
The water and land management is an important aspect in watershed programme increasing the productivity visa- vis sustainability of resources. Watersheds are natural hydraulic entity where water flows in a definite path to a common point. For land use planning of any watershed, soil characterization for its area is very essential and important. This would help in knowing the soil fertility status in watershed area. GIS is a tool that can be effectively used for spatial analysis of soil fertility for a desired geographical area. Domagor-Pahuj watershed is situated in Jhansi district of Bundelkhand region and located between 25o28’ to 25o31’ N latitude and 078o25’ to 078o28’ E longitude. This watershed has a total geographical area of 1 646 ha out of which 1 373 ha area is treatable and consists of three villages namely Domagor, Dikauli and Naya Khera. A total number of 103 representative soil samples were taken from Domagor-Pahuj watershed during May-June 2010. These samples were analyzed for soil parameters like pH, OC, EC, P, K, Zn, B and S. These sample points were geographically referenced and soil maps were generated using Geostatistical interpolation methods in Arc GIS 10. Ordinary and Universal Krigging methods were applied and compared on the basis of RMSE. Out of the two methods applied, ordinary Kriging was found better for prediction of soil EC, P, B and S, whereas universal Krigging was found better for prediction of soil pH, OC, K and Zn. Thus, spatial maps were generated by Ordinary and Universal Krigging methodsfor these soil parameters and hence may be used for soil fertility status and land use planning of Domagor-Pahuj watershed.